Effects of Polyphenols Extracted from Tamarind (Tamarindus indica L.) Seed Coat on Differential White Blood Cell Count in Broilers (Gallus domesticus) Exposed to High Environmental Temperature - Aengwanich, W.; Suttajit, M.; Narkkong, N.A. (International Journal of Poultry Science, 2009)
Tamarind (Tamarindus indica L.) is a plant that belongs to the Leguminosae family and grows naturally in tropical and subtropical regions. Tamarind seed coat is composed of polyphenols especially procyanidin oligomers. The objective of this experiment was to determine the effect of polyphenols extracted from tamarind seed coat on differential white blood cell counts of broilers maintained at high environmental temperature. Broilers were divided into 2 groups. In group 1, broilers were maintained in environmental temperature at 26±2oC throughout experimental period, and in group 2, broilers were maintained in environmental temperature at 38±2oC and received polyphenols i.e. 0, 100, 200, 300, 400 and 500 mg/kg in diets. Differential white blood cell counts were investigated on days 1, 7, 14 and 21 of experimental period. The results revealed the following information: Lymphocyte and basophil levels of broilers maintained in the environmental temperature at 38±2oC and received polyphenols at 400 mg/kg in diet were increased (p